Think Twice When Using Melatonin to Aid Sleep: New Research Links its Use to Heart Failure Risk - Cock, Ian E (Pharmacognosy Communications, 2026)
Melatonin is commonly used to assist in with sleep disorders and its use is generally regarded as harmless. However, a recent report by the American Heart Association1 has highlighted previously unreported risks to cardiac function with its use. Indeed, patients that used melatonin continuously for a year or more were 3.5 times as likely to be hospitalised with cardiac failure than the rest of the population. Furthermore, cardiac-related mortality was reported to be approximately twice as frequent in long-term users than in the general population. Whilst this study did not definitively establish melatonin as the direct cause of cardiac failure, the correlation between its use and the negative outcomes are cause for concern and the American Heart Association advises caution with long-term melatonin use.
Keywords: The Janus Corner